(untitled) (Praxis Educativa, 2023)
This article studies the experiences of schooling during the pandemic in Argentina and identifies the relationship between digital technologies and inequalities. We present quantitative and qualitative results of two research projects that inquired about the daily life of families in Argentina based on the analysis of access to technological devices and the forms of pedagogical accompaniment and the development - or not - of the necessary skills. Among the most relevant results we find that the socioeconomic level and the social, cultural and educational trajectories of the adults in charge were crucial factors when evaluating the ways in which the period without face-to-face classes was traversed. Added to this, the conditions of access to digital technologies, the virtual education dynamics proposed by the institutions, and the digital skills that mothers and fathers possessed, or were able to develop, resulted in different and unequal schooling experiences during the pandemic.